Palmitic acid induces endoplasmic reticulum stress in AML12 liver cells - BATIREL, SAİME (MARMARA UNIV, FAC MEDICINE, 2018)
Objectives: Non-alcoholic fatty liver disease (NAFLD) is characterized by increased fatty acid levels in serum and liver. The mechanism of NAFLD is unclear. The role of endoplasmic reticulum (ER) stress attracts attention. First aim of this study was to design an in vitro NAFLD model. The effects of palmitic acid (PA) alone or combination with oleic acid (OA) on intracellular reactive oxygen species (ROS) production and ER stress in liver cells were investigated as a second aim. Materials and Methods: AML12 cells were exposed to PA and/or OA with different concentrations and combinations. Intracellular lipids and cell viability were detected with Oil red O staining and WST-1 assay respectively. Intracellular ROS accumulation was measured by flow cytometry analysis. Expression of ER stress proteins, immunoglobulin binding protein (BiP) and IRE1, were evaluated with western blot analysis. Results: Intracellular lipid content was increased in all treated groups. Cell viability was decreased whereas ROS generation and expression of the ER stress proteins were increased in cells treated with PA. However, these effects were not observed in the cells treated with OA+ PA combination. Conclusion: PA induces ROS generation and the ER stress pathway that is mediated by IRE1 in liver cells. Addition of OA enhances these effects.
Keywords: Non-alcoholic fatty liver disease; Palmitic acid; Oleic acid; Endoplasmic reticulum stress; NONALCOHOLIC STEATOHEPATITIS; HEPATIC STEATOSIS; MOLECULAR-MECHANISMS; OXIDATIVE STRESS; RAT HEPATOCYTES; APOPTOSIS; CYTOTOXICITY; PATHOGENESIS; ACTIVATION; INDUCTION